Corporate governance post-Enron: Effective reforms, or closing the stable door? - Gillan, Stuart L.; Martin, John D. (Journal of Corporate Finance, 2007)
We examine Enron's collapse to provide insights as to the efficacy of recent governance reforms. In doing so, we explore two main issues. First, if recently mandated governance changes had been in place earlier, would they have constrained actions by Enron's management? Second, and more generally, which of the recent governance changes might act to constrain governance failures going forward? Although many aspects of corporate governance failed at Enron, the firm's viability ultimately rested on an inherently risky business strategy, a strategy that the board and others apparently failed to understand. However, it is not apparent that increasing board independence would have changed Enron's strategic direction, or prevented the firm's collapse. From this perspective, many recent reforms, including those mandating specific board structures likely move firms away from their optimal governance structure and are tantamount to closing the stable door after the horse has bolted. We assert that, ceteris paribus, stronger internal controls coupled with reduced potential for conflicts of interest on the part of the external auditor might have constrained management's ability to hide the firm's true financial condition and are likely to constrain aspects of fraudulent behavior going forward.